2009
DOI: 10.1002/pssa.200925009
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and piezoelectric properties of Li‐doped Bi0.5(Na0.825K0.175)0.5TiO3 piezoelectric ceramics

Abstract: 1618Xiaoming Chen et al.: Li-doped Bi 0.5 (Na 0.825 K 0.175 ) 0.5 TiO 3 piezoelectric ceramics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…5 shows the temperature dependence of relative permittivity ε r and dielectric loss tanı of BNKT17.5 ceramics sintered at 1150 • C and measured at different frequencies. It can be seen that the ceramics exhibit two phase transitions at T d and T m , which are consistent with the BNT-based ceramics [3,7,20]. T d is the depolarization temperature at which tanı reaches the first peak and corresponds to the transition from a ferroelectric phase to an "antiferroelectric" phase, while T m is the maximum temperature at which ε r gets to a maximum value and corresponds to a transition from an "anti-ferroelectric" phase to a paraelectric phase [21].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…5 shows the temperature dependence of relative permittivity ε r and dielectric loss tanı of BNKT17.5 ceramics sintered at 1150 • C and measured at different frequencies. It can be seen that the ceramics exhibit two phase transitions at T d and T m , which are consistent with the BNT-based ceramics [3,7,20]. T d is the depolarization temperature at which tanı reaches the first peak and corresponds to the transition from a ferroelectric phase to an "antiferroelectric" phase, while T m is the maximum temperature at which ε r gets to a maximum value and corresponds to a transition from an "anti-ferroelectric" phase to a paraelectric phase [21].…”
Section: Resultssupporting
confidence: 81%
“…Meanwhile, the dielectric loss increases with temperature and reaches the first peak at T d , and then decreases with temperature due to less distortion in the crystal structure after depolarization [22,23]. Additionally, the curie temperature (300 • C) is very close to an early result obtained from BNT-BKT ceramics prepared by the conventional solid-state reaction method [19,20].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Although the enhanced electric properties of BCTZL ceramics can be related to dense ceramics [17,39], oxygen vacancies [37,38], grain size effects [40], the phase evolution [29], it can be mainly attributed to the fact that the PPT temperature (O-T transition temperature) of BCTZL ceramics above T sin = 1350°C are approximate to room temperature (as shown in Fig. 6), and then the ceramics can easily go through the phase evolution from O to T phase at room temperature, which make ferroelectric domains easily switch and produce large piezoelectric response.…”
Section: Resultsmentioning
confidence: 99%
“…The Li + -containing additives as a sintering aid of low valence can decrease the sintering temperature without sacrificing the electric properties of BaTiO 3 lead-free ceramics, where Li ions can incorporate into the lattice of BaTiO 3 [17][18][19] during the sintering process. Haussonne et al [20] reported that a perovskite phase (BaTi (1Àx) Li x O (3À3x) F 3x ) was formed by addition of 1-2 wt.% LiF to BaTiO 3 during liquid phase sintering, which contributes to the densification behavior and good dielectric properties.…”
Section: Introductionmentioning
confidence: 99%